1 0 0 x 2 − 6 x + 1 + 5 = 1 0
Find the sum of all the roots that satisfy the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great job,here's a tip!.At last we get an equation 2 x 2 − 1 2 x + lo g 2 + 1 = 0 . Then we can simply use Vieta's to get the sum of root as − 2 − 1 2 = 6 . Also,you can make your solutions more attractive and easy to understand with L A T E X .See this .
1 0 0 x 2 − 6 x + 1 + 5 = 1 0 1 0 0 x 2 − 6 x + 1 = 5 lo g 1 0 ( 1 0 2 ) x 2 − 6 x + 1 = lo g 1 0 5 2 ( x 2 − 6 x + 1 ) = lo g 1 0 5 x 2 − 6 x + 1 = 2 lo g 1 0 5 x 2 − 6 x + 1 − 2 lo g 1 0 5 = 0
Given that x 2 − ( Sum of roots ) x + ( Product of roots ) = 0
Sum of roots = 6
1 0 0 x 2 − 6 x + 1 = 5 , which, when take log 100, gives x 2 − 6 x + 1 = lo g 5 , or simply ( x − 3 ) 2 = 8 + lo g 5 Hence, x = 3 ± 8 + lo g 5 , and their sum is 6.
Problem Loading...
Note Loading...
Set Loading...
The solution to this problem is:
Step 1: 1 0 0 x 2 − 6 x + 1 + 5 = 1 0
Step 2: 1 0 0 x 2 − 6 x + 1 = 1 0 − 5
Step 3: 1 0 0 x 2 − 6 x + 1 = 5
Step 4: ln ( 1 0 0 x 2 − 6 x + 1 ) = ln ( 5 )
Step 5: ( x 2 − 6 x + 1 ) × ln ( 1 0 0 ) = ln ( 5 )
Step 6: x 2 − 6 x + 1 = ln ( 1 0 0 ) ln ( 5 )
Step 7: Solve the quadratic equation to find the values of x which will be: x = 5 . 8 8 9 5 4 7 5 4 2 8 2 and x = 0 . 1 1 0 4 5 2 4 5 7 1 8 5
Step 8: Add 5 . 8 8 9 5 4 7 5 4 2 8 2 and 0 . 1 1 0 4 5 2 4 5 7 1 8 5
Step 9: The answer will be 6
WRITE THESE STEPS IF YOU GOT WRONG TO HAVE A CLEARER UNDERSTANDING.
THANK YOU.